2019
DOI: 10.1177/2050312119850390
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in primary Sjögren’s syndrome: A proteomic pilot study of cerebrospinal fluid

Abstract: Objectives: Fatigue is a frequent and often disabling phenomenon that occurs in patients with chronic inflammatory and immunological diseases, and the underlying biological mechanisms are largely unknown. Because fatigue is generated in the brain, we aimed to investigate cerebrospinal fluid and search for molecules that participate in the pathophysiology of fatigue processes. Methods: A label-free shotgun proteomics approach was applied to analyze the cerebrospinal flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…There were five upregulated DEGs in our results, as shown in Figure 3 ( CFB, CFI, C2, C4A/B, and SERPING1) . CFB, a component of the alternative pathway of complement, is also increased in cerebrospinal fluid of patients with SS and fatigue ( 41 ). Both C2, C4A, and C4B proteins are known to participate in the generation of the classical complement pathway.…”
Section: Resultsmentioning
confidence: 99%
“…There were five upregulated DEGs in our results, as shown in Figure 3 ( CFB, CFI, C2, C4A/B, and SERPING1) . CFB, a component of the alternative pathway of complement, is also increased in cerebrospinal fluid of patients with SS and fatigue ( 41 ). Both C2, C4A, and C4B proteins are known to participate in the generation of the classical complement pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The biological mechanisms involved in pSS fatigue are still not fully understood. Recent studies using proteomic analysis have shown the expression of proteins in the blood (SNAP-25, ENO1, UCHL1, IL-36a and complement factors) and in the CSF (apolipoprotein-A4, hemopexin, pigment epithelium-derived factor, secretogranin-1, secretogranin-3, selenium-binding protein-1, and complement factor B) in fatigued compared to non-fatigued pSS (13,26). With important roles in regulation of innate immunity, cellular stress defense, and/or functions in the central nervous system, supporting the hypothesis that fatigue signaling pathways appear to be more associated with cell protection and defense than with pro-inflammatory pathways and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Among these were apolipoprotein-A4, hemopexin, pigment epithelium-derived factor, secretogranin-1, secretogranin-3, selenium-binding protein-1, and complement factor B, with important roles in regulation of innate immunity, cellular stress defense, and/or functions in the central nervous system, and some downregulate inflammation. An important sleep regulator, Hypocretin-1, was also increased in pSS and can influence fatigue by an IL-1b independent mechanism (26).…”
Section: Biomarkers To Understand Fatiguementioning
confidence: 99%
“… 32 34 38–42 There were no direct associations with SNPs in genes coding for cytokines in our data, but as discussed above the pathways of the immune system are complex and it is difficult to pinpoint one specific cytokine or molecule, rather a number of signalling pathways interact and generate fatigue. 32 …”
Section: Discussionmentioning
confidence: 58%
“…Complement factor B has been associated with fatigue in a proteomics study of cerebrospinal fluid (CSF) in pSS. 32 To further characterise a possible functional impact of genetic variants in pSS-related fatigue, we assessed gene and protein expression levels of RTP4 in pSS patients. Increased mRNA expression of RTP4 in patients compared with controls was found in peripheral B cells, supporting the hypothesis of a putative functional role for RTP4 in fatigue.…”
Section: Discussionmentioning
confidence: 99%